Coexisting tuberculosis of middle ear and maxillary sinus: a rare presentation - Singh, Amardeep; Kumar, Navneet; Kwatra, Kanwardeep Singh (International Journal of Research in Medical Sciences, 2017)
Coexisting tuberculosis of middle ear and paranasal sinuses is a diagnostic challenge due to rarity of occurrence and clinically variable presentation. A case of tuberculous otitis media along with involvement of maxillary sinus is reported. The patient presented with bilateral ear and nasal discharge for 4 years. Symptoms used to get partially alleviated with standard antimicrobial therapy. Otoscopy showed bilateral large, central perforations of tympanic membrane with granulations in the middle ear. In the nasal cavity, mucopurulent discharge was noted with crust formation. Pure tone audiometry (PTA) showed 63.3 dB moderately severe mixed hearing loss in right ear and 83.3 dB severe mixed hearing loss in the left ear. Patient underwent cortical mastoidectomy and tympanoplasty on left side with middle meatal antrostomy on right side. Pale granulation tissue from middle ear and mastoid as well as unhealthy mucosa from maxillary sinus was sent for histopathological evaluation which revealed a diagnosis of tuberculosis. On further work up patient was found to be sputum positive for acid fast bacilli (AFB). Antitubercular therapy was initiated with good follow-up response. Middle ear and maxillary sinus are rare sites involved in tubercular infections. Isolated cases of tuberculous otitis media or maxillary sinus have been reported but concomitant involvement of both these sites has not been reported in the available literature.